Quantitative analysis of led for urban green wall - Lee, Jun Da (2016)
Green walls, also known as living walls, are slowly gaining popularity in our modern society due to the long lists of benefits that comes along with it. Some benefits are known to improve the aesthetics of our urban cities and also the well being of people. As green wall is still a relatively new technology, there is still high operational costs involved and a lack in quantitative data of how the plants on the green wall are doing. Hence this experiment is conducted in collaboration with Greenology Pte Ltd to find out the optimum light angle that allows plants to grow best on green walls, which can potentially cut down future costs to maintain it. Light intensity is vital to plant growth. Plant growth is also observed throughout a span of 8 weeks by growing plants under three different light angles on the green wall. Node lengths and colour of leaves of the plants will be compared to determine which light angle is the best for plant growth for the green wall. Results based on the experiment showed that plants thrive better under light angle 80° judging from the state of the leaves and the node lengths. Further improvements that can be done such as additional lightings and changes to irrigation system are also discussed.